Parameterizing the Heterogeneous Liquid‐Ice Mixing in Modeling Ice Growth Through the Wegener‐Bergeron‐Findeisen Process in CAM6 - Jing Yang; Jianqiao Lu; Yuting Deng; Yong Wang; Chunsong Lu; Yan Yin; Zhien Wang; Xiaoqin Jing; Kang Yang (Geophysical Research Letters)
Abstract Accurate representation of cloud phase partitioning is critical for understanding the cloud feedback to climate change, but the supercooled liquid fraction is often underestimated in global climate models, in part due to the assumption of homogeneous distributions of hydrometeors in mixed‐phase clouds. In this study, we take into account the heterogeneous liquid‐ice mixing in modeling the ice depositional growth using airborne in situ measurements. The impact of heterogeneous liquid‐ice mixing on the Wegener‐Bergeron‐Findeisen process is parameterized as the fraction of ice that is mixed with liquid water, which is a function of liquid‐ice mixing homogeneity and liquid fraction. The liquid‐ice mixing homogeneity, quantified using the information entropy theory, is parameterized using the total condensed water content and temperature. With this observationally constrained parameterization incorporated in the Community Atmospheric Model version 6, the modeled cloud phase partitioning and cloud radiative forcing are improved.